UTILIZATION OF LANDFILL LEACHATE AS LIQUID ORGANIC FERTILIZER THROUGH FERMENTATION PROCESS WITH THE ADDITION OF AZOSPIRILLUM SP. - Wulandari, Salsabila Puspita; Nisa’, Syadzadhiya Qothrunada Zakiyayasin (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2024)
This study investigates the utilization of landfill leachate as a raw material for producing liquid organic fertilizer (LOF) through a fermentation process with the addition of Azospirillum sp. The research focuses on evaluating the effects of different dilution levels (20×, 40×, 60×, and 80×) and a 14-day fermentation period under anaerobic conditions on the quality of the resulting fertilizer. The results showed that the 20× dilution produced the most optimal conditions, yielding macronutrient contents (N, P₂O₅, and K₂O) that met the national quality standards for liquid organic fertilizer. Additionally, a decrease in heavy metal concentration, particularly Lead (Pb), was observed during fermentation, indicating improved environmental safety of the final product. Although the C-organic and Fe contents were below the required limits, the neutral pH and absence of microbial contamination confirmed that the fertilizer is environmentally safe for agricultural application. Overall, this study demonstrates that the fermentation of landfill leachate with the addition of Azospirillum sp. provides a sustainable and eco-friendly approach for converting waste into a value-added product that supports environmentally responsible agriculture.